THE ROLE OF GLOBALISATION IN THE STRATEGIC DEVELOPMENT OF UKRAINIAN ENTERPRISES - Vadym Sharapa (Izdevnieciba "Baltija Publishing", 2023)
The article analyses the characteristics, criteria and various factors influencing the impact of globalisation on economic development and business activity in contemporary Ukraine. At present, society is facing new goals, tasks and requirements, which are largely determined by scientific and technological progress, implementation of innovative technologies and the need for a certain degree of flexibility, resilience and adaptation to dynamic changes in the economic sector. At this stage, financial stability and prosperity are among the most important values in the modern world, and this is driving the interest in studying the peculiarities of innovative economic development. At the same time, globalisation issues remain understudied and require an analysis of specific "parallels" between past and present outcomes. This analysis helps to identify the "gaps" and "risk zones" within the global market, which is crucial for all countries participating in these market relations. The subject of the study is globalisation as a driving force for the development of enterprises in Ukraine. An assessment of the dynamics of the crisis' impact on Ukrainian business, based on a survey conducted by EKONOMICHNA PRAVDA in 2020-2023, leads to the following conclusions: approximately 25% of the establishments that existed and successfully operated in Ukraine before 2020 have closed; the quarterly drop in revenue in the most successful restaurants is approximately 30-35%; staff loss or shortage is about 48%; and approximately 80% of establishments are experiencing logistical problems (Business and the Crisis in Ukraine). The purpose of the research is to assess the current state of development of enterprises in Ukraine and to study potential opportunities for optimising their activities in view of globalisation. Methodology. Definition of conceptual apparatus, analysis, synthesis and synthesis of information on the relevant issue. Conclusion. The destructive and destabilising processes that pose challenges to the development of Ukrainian businesses are characterised by a high degree of risk and uncertainty in the context of Russia's full-scale war against Ukraine. The following components must be taken into account: political factors: an unfavourable situation caused by military aggression, the need for additional alerts in case of emergencies and to ensure the safety of customers; additional expenses: generators, security systems and video surveillance; economic factors: rising prices of domestic goods and products; the need to create a new service concept that stands out from the competition.